A policy feedback and socio-technical approach to e-participation (PFSTEP): A cross-national analysis of technology and institutions to explain e-participation. Issue 2 (3rd April 2021) - Rawat, Pragati
ABSTRACT: This paper aims at explaining the difference in e-participation (or online public participation) across countries using a conceptual model that is quantitatively analyzed using panel data. The model is based on the theories of policy feedback and socio-technical approach in the participation literature and explores the mediating and moderating role of technology on institutions. The technology variable is measured along four dimensions of information and communication technology (ICT), namely, infrastructure, affordability, skills, and usage. The institutions variable is measured along the two dimensions of political and regulatory environment and political rights and civil liberties. The study is significant as it quantitatively analyzes a complex longitudinal relationship between institutions, technology, and e-participation and finds support for institutions' role as antecedents to technology. Findings inform that ICT skills play a mediating role while ICT infrastructure and usage act as moderator for institutions' impact on e-participation.